Kekayaan Intelektual: Studi Literatur Review Permasalahan Etika Pada Teknologi Informasi - billi (Institute of Information Technology and Social Science (IITSS), 2020)
In the dynamics involving advances in information technology, intellectual property emerges as a central element that links creativity and legal rights in the digital sphere. This article summarizes the literature related to intellectual property and the ethical challenges that accompany it in the context of information technology. Copyrights, patents, trademarks and business secrets form the main foundation of intellectual property, forming a legal and normative framework that supports innovation. However, as technology grows, deep ethical issues surrounding intellectual property rights emerge. By analyzing key concepts and current findings in the literature, this article attempts to assemble a balanced and holistic view of emerging ethical issues. It is hoped that a better understanding of these dynamics can help shape ethical frameworks that promote innovation, while respecting intellectual property rights. Through this literature review, we are invited to explore the ethical dimensions of managing intellectual property in the era of information technology, leading us towards a more solid and sustainable ethical foundation in an ever-evolving digital world. Kata kunci: Intellectual Property, Ethics, information technology